without using a truth table prove the following:

(j--->a) and (s--->h) and (j or s) ---> (a--->j) or (h--->s)

2 posts
• Page **1** of **1**

without using a truth table prove the following:

(j--->a) and (s--->h) and (j or s) ---> (a--->j) or (h--->s)

(j--->a) and (s--->h) and (j or s) ---> (a--->j) or (h--->s)

- beast
**Posts:**1**Joined:**Mon Oct 21, 2013 3:01 am

beast wrote:without using a truth table prove the following:

(j--->a) and (s--->h) and (j or s) ---> (a--->j) or (h--->s)

I would suggest proceeding by contrapositive or contradiction. Make assumptions about the "then a-then-j or h-then-s", and see where this leads.

If you are working with a different method of your preference, kindly please reply with your efforts thus far. Thank you.

- nona.m.nona
**Posts:**256**Joined:**Sun Dec 14, 2008 11:07 pm

2 posts
• Page **1** of **1**